2021
DOI: 10.1002/jat.4212
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to crystalline silica and peripheral biomarkers: An update

Abstract: Peripheral biomarkers are important tools for detecting occupational exposures to prevent the onset and/or progression of diseases. Studies that reveal early peripheral biomarkers are highly important to preserve the health of workers and can potentially contribute to diagnosing and/or prognosing occupational pathologies. Exposure to crystalline silica is a problem in several workplaces because it increases the risk of chronic obstructive pulmonary disease (COPD), tuberculosis, cancer, and pulmonary fibrosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
5
0
2
Order By: Relevance
“…Some of the introduced modifications can also consider the latest research results. In recent papers the authors discuss the use of some other diagnostic tools and new methods for early silicosis detection, like high resolution computed tomography (HRCT), ultra-low dose computed tomography (ULD-CT), alveolar crystal burden quantification in bronchoalveolar lavage (BAL), biomarkers present in serum or exhaled breath condensate (EBC) [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the introduced modifications can also consider the latest research results. In recent papers the authors discuss the use of some other diagnostic tools and new methods for early silicosis detection, like high resolution computed tomography (HRCT), ultra-low dose computed tomography (ULD-CT), alveolar crystal burden quantification in bronchoalveolar lavage (BAL), biomarkers present in serum or exhaled breath condensate (EBC) [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…However, these oxidative, inflammatory and immunological biomarkers are usually not very specific. Further studies also found serum Clara cell protein-16 (CC16) and l-selectin levels could be good biomarkers of pneumoconiosis effect, and neopterin levels in urine and serum may be good exposure biomarkers [ 44 ]. However, large sample epidemiological studies and are still needed for population verification, especially in combination with a large number of different types of people, including pneumoconiosis, healthy control and even nonpneumoconiosis workers exposed to occupational dust.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker studies of CS exposed humans have focused on inflammation, pneumoproteins and other types of biomarkers, and the results have often been inconsistent (BlancoPérez et al 2021 ; Peruzzi et al 2022 ; Călutu et al 2023 ). This may partly be related to the selection of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…
The mechanisms of pulmonary CS toxicity have not been completely elucidated. Proposed mechanisms include destruction of pulmonary surfactant or the modification of silica toxicity by surfactant covering the particles, the ability of CS to form free radicals, surface chemistry, the ability to increase lysosomal permeability and the role of silica to induce macrophage immune dysfunction (Hamilton et al Jr 2008;Pavan et al 2019).Biomarker studies of CS exposed humans have focused on inflammation, pneumoproteins and other types of biomarkers, and the results have often been inconsistent (Blan-coPérez et al 2021;Peruzzi et al 2022;Călutu et al 2023). This may partly be related to the selection of subjects.
…”
mentioning
confidence: 99%